Learn C++ for game development - Sutherland, Bruce (Video game developer) (Expert's voice in game development., 2014)
"If you're new to C++ but understand some basic programming, then Learn C++ for Game Development lays the foundation for the C++ language and API that you'll need to build game apps and applications. Learn C++ for Game Development will show you how to: Master C++ features such as variables, pointers, flow controls, functions, I/O, classes, exceptions, templates, and the Standard Template Library (STL); Use design patterns to simplify your coding and make more powerful games; Manage memory efficiently to get the most out of your creativity; Load and save games using file I/O, so that your users are never disappointed. Most of today's popular console and PC game platforms use C++ in their SDKs. Even the Android NDK and now the iOS SDK allow for C++; so C++ is growing in use for today's mobile game apps. Game apps using C++ become much more robust, better looking, more dynamic, and better performing. After reading this book, you'll have the skills to become a successful and profitable game app or applications developer in today's increasingly competitive indie game marketplace. The next stage is to take the foundation from this book and explore SDKs such as Android/Ouya, PlayStation, Wii, Nintendo DS, DirectX, Unity3D, and GameMaker Studio to make your career really take off. What you'll learn: How to use the various C++ skill fundamentals: variables, pointers, flow controls, functions, I/O, classes, exceptions, and more; How to write C++ games using object-oriented programming techniques: classes, objects, inheritance, and polymorphism; How to use templates and the Standard Template Library (STL) in C++; How to work with design patterns in C++ game development; How to apply C++ to native game activities; How to master concurrency and the gains in performance it brings. This book is for aspiring game developers with some previous programming experience who need to learn the critical C++ skills necessary to build game applications. C++ is the most popular programming language in use behind most game applications."--